2009
DOI: 10.1108/02683940910922528
|View full text |Cite
|
Sign up to set email alerts
|

Organizational justice and managerial commitment in corporate mergers

Abstract: PurposeThe purpose of this paper is to investigate whether perceptions of distributive, procedural and interactional justice can explain the frequently reported low organizational commitment of managers in corporate mergers. Specifically, it aims to examine whether each of the justice dimensions is significantly and uniquely related to affective commitment, which of the justice dimensions has the strongest relationship with the criterion, and whether instrumental evaluations or trust might function as a mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 37 publications
2
75
1
1
Order By: Relevance
“…Masterson (2001) explained that distributional and political justice relate to commitment. In a research conducted by Klendauer and Deller (2009), it is shown that every dimension of justice relates to effective commitments positively; if people feel that there is no discrimination between distributing rewards, decisions methods and interaction among people in the organization, they make themselves committed to the organization. Shafeepour Motlaq's (1998) research shows that if no discrimination is observed by employees in an organization, they will be motivated to work in the best possible way.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Masterson (2001) explained that distributional and political justice relate to commitment. In a research conducted by Klendauer and Deller (2009), it is shown that every dimension of justice relates to effective commitments positively; if people feel that there is no discrimination between distributing rewards, decisions methods and interaction among people in the organization, they make themselves committed to the organization. Shafeepour Motlaq's (1998) research shows that if no discrimination is observed by employees in an organization, they will be motivated to work in the best possible way.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Contents of the questionnaire used in this research were taken from various researchers' work. Scale of organizational justice is taken from researcher Klendauer & Deller (2009) work. Scale of overall job satisfaction was adopted from Lu et al (2007).…”
Section: Instrument Usedmentioning
confidence: 99%
“…Indubitably, it is of paramount importance that organizations convince employees about management sincerity in ensuring equity in information sharing. Strategic manipulation intentions may generate counterproductive effects (Klendauer and Deller, 2009) that can spiral beyond managerial control. Moreover, providing adequate explanations for decisions and events that affect them improve job satisfaction.…”
Section: Managerial Implications and Contributionsmentioning
confidence: 99%
“…Therefore, prompt and honest feedback is essential to maintain trust and confidence in managerial decisions. As perception of justice is formed quickly, inadequate information in decision-making may influence the perception of subsequent actions (Klendauer and Deller, 2009). Indubitably, it is of paramount importance that organizations convince employees about management sincerity in ensuring equity in information sharing.…”
Section: Managerial Implications and Contributionsmentioning
confidence: 99%